Re-thinking Other Claimants to Prophethood: the Case of Umayya ibn Abi Salt - Al Makin (Al-Jami'ah Research Centre, 2010)
This article questions the domination of the prophethood of Muhammad in the narrative of the seventh century of the Arabian Peninsula presented by both Muslim and Western scholars. There were many other claimants to prophethood, who are ignored in Muslim and Western sources. In this vein, this article deals with Umayya ibn Abi Salt, a poet who claimed prophethood. Umayya’s short biography, collections of his poems (diwan) and , and examples of his poems are discussed.